Far and near fields of Hermite–Gaussian beams passing through an annular aperture and its numerical simulation by the angular spectrum method - Talatinian, Alexander (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
This research focuses on the analysis of the free propagation of Hermite–Gaussian beams diffracted by a symmetrical annular aperture placed at the beam waist plane. The propagation is studied analytically and numerically using the angular spectrum method and the 2D fast Fourier transformation. Numerical simulation examples illustrate the propagation characteristics of the Hermite–Gaussian beams diffracted by an annular aperture. The beam truncation parameters and obscuration ratio inﬂuence Hermite–Gaussian beam diffraction properties.
Optica Applicata, Vol. 53, 2023, nr 3, s. 467-481
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; angular spectrum; propagation of higher modes; annular aperture; near-and far fields